Epidemiological Trends of Tuberculosis in Low and High Prevalence Countries - Bleiker, M.A. (Paediatrica Indonesiana, 2017)
The study of the epidemiology of tuberculosis and the need for a rational approach to the problem of tuberculosis control require a sound knowledge of the risk of transmission of tuberculosis infection from host to host. This knowledge is required today both in countries with a high prevalence and in those with a low prevalence of the disease. The risk of transmission of tuberculosis infection in a given community during a particular period of time is most reliably expressed numerically in terms of a series of average annual infection risks in successive calender years. The infection risk indicates the proportion of the population which will be primarily infected, or reinfected, with tubercle bacilli in the course of one year. The risk is usually expressed as a percentage or as a rate. The annual trend (decrease) in the risk of infection is even more important than the actual level of this risk. Tuberculin surveys in schoolchildren, which are repeated, say every five years, in the same area provide us with the necessary information to make estimates for the annual infection risk. In areas where infections with the socalled atypical mycobacteriae are frequent, simultaneous testing with two "Sensitins", one prepared from human tubercle bacilli and one from atypical mycobacteriae will be of value for estimating the proportion of those infected with virulent bacilli and those infected with other mycobacteriae.